(The Use of Pineapple Puree, Sweet potato and Nata de Coco on the Preparation of Dried Functional Snack) - Maman Rohaman, M; Nurlaelyah, Elly (Warta Industri Hasil Pertanian, 2000)
Research on the preparation of dried functional snack has been conducted. The formulation was development based on sweet potato leather of pineapple puree 150 and 300 g, nata de coco 0, 100, 200, and 300 g withsweet potato 500 g respectively. The products were stored for 0,4,8 and 12, weeks. The result showed that the effect of storage gave the decrease of moinsture, protein and sugar content for the addition of each nata de coco, while the effect of storage gave the increase of Ph for the addition of each pineapple puree. The dietary fibre and microbial content were relatively unchanged during storage. The best product was accepted by the panelist with the formulation i.e. pineapple puree 150 g, nata de coco 100 g and sweet potato 500 g.